Analisi fitosociologica e valutazione agronomica di pascoli subalpini - Scotton, Michele; Rodaro, Paolo; Ziliotto, Umberto (EUT Edizioni Università di Trieste, 1996)
PHYTOSOCIOLOGICAL ANALYSIS AND AGRONOMIC EVALUATION OF SUBALPINE PASTURES (MALGA PADEON, CORTINA D'AMPEZZO, NE ITALY). In this study the vegetation and the agronomic evaluation of subalpine pastures are described. These pastures are developed from 1800 to 2100m on calcareous soils and have not been used for grazing since the early '80s. The following vegetation types have been identified: Poa alpina pasture (Poion alpinae), Carex davalliana fen (Caricetum davallianae), Carex ferruginea pasture (Caricerum ferrugineae trifolietosum), Sesleria albicans pasture (Carici ornithopodae-Seslerietum albicantis), calcareous scree community (Thlaspictea rotundifolii), Pinus mugo scrub (Erico-Rhododendretum hirsuti) and Pinus cembra wood (Vaccinio-Pinetum cembrae rhododendrerosum hirsuti). The ecological evaluation of the vegetation types was based on an indirect analysis by means of the Landolt indeces. Some dynamic trends have been hypothesized on the basis of the ecological characterization. The indirect agronomic evaluation of the pasture types was based on the goodness values (Gütenzahl) of each species